Dielectric properties and microstructural studies of Er2O3doped potassium sodium niobate silicate glass-ceramics - Ploypailin Yongsiri (2018)
© 2018 Trans Tech Publications, Switzerland. In this work, electrical and structural properties of ferroelectric glasses and glass-ceramics from K0.5Na0.5NbO3-SiO2doped with 0.5-1.0 mol%Er2O3system have been investigated. The influent of Er2O3dopant was also compared with the original glass. The K0.5Na0.5NbO3(KNN) powder was mixed with SiO2in composition of 75KNN-25SiO2and doped with Er2O3. Well-mixed powder was subsequently melted at 1300oC for 15 min in a platinum crucible using an electric furnace. The quenched glasses were then subjected to heat treatment at various temperatures for 4 h. From the study, KNN single phase in transparent glass was successfully prepared via incorporation method. The maximumrof about 360 at 10 kHz with a low tanδ of 0.07 could be obtained from the glass-ceramic sample of 75KNN–25SiO2doped 0.5 mol% Er2O3and heat treated at 600C. It can be seen that the higher percent of Er2O3can lower the dielectric loss of KNN glass-ceramics. This interesting value suggesting the opportunity of using them in electronic applications in the future.